Free Convection from a Vertical Permeable Circular Cone with Pressure Work and Non-Uniform Surface Temperature - Alam, Md. M. M.; Alim, M. A. A.; Chowdhury, Md. M. K. M. K. (Nonlinear Analysis: Modelling and Control, 2007)
Laminar free convection from a vertical permeable circular cone maintained at non-uniform surface temperature with pressure work term is considered. Non-similarity solutions for boundary layer equations are found to exist when the surface temperature follows the power law variations with the distance measured from the leading edge. The numerical solutions of the transformed non-similar boundary layer equations are obtained by using two methodologies, namely, (i) a finite difference method and (ii) a series solution or perturbation method for small values of ξ, the dimensionless suction parameter. Solutions obtained in terms of skin-friction coefficient, local rate of heat transfer, velocity and temperature profiles for the values of Prandtl number, pressure work parameter and temperature gradient are displayed in both graphical and tabular forms. Finite difference solutions are compared with the solutions obtained by perturbation technique and found to be in excellent agreement near the leading edge.